EU - Australia. Economic Partners? - Żołądkiewicz, Krystyna (UE - Australia. Partnerzy handlowi?, 2010)
The European Union (EU) remains among Australia's largest single trading partners. Economic relations between the EU and Australia have longstanding tradition and are based on diversified commercial and investment links. On the other hand, however, over the past 20 years Australia has been immensely expanding trade with Asia. Countries from Asia accounted for six out of Australia's top ten trading partners in 2008-09, accounting to 44.9% share of Australian total trade, and these were China, Japan, Republic of Korea, Singapore, India, and Thailand. Asia, one of the fastest growing regions in the world, will continue to drive Australia's trading performance in years to come, which may results in declining the role of the EU.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 126, s. 247-256
Keywords: European Union; Australia; economic partners; cooperation